Implementasi Pembelajaran PAI Dalam Pembentukan Karakter Religius Peserta Didik di SMP Muhammadiyah 48 Medan - Ulfah, Syarifah Widya; Nurfadillah, Ainaya; Amanda, Fitry; Nurhikmah, Rizky Arafani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The development of science and technology has a negative impact on the character of a nation. To overcome this impact, it is necessary to implement character education in educational institutions. This study aims to determine the implementation of PAI learning in shaping the religious character of students at SMP Muhammadiyah 48 Medan and its supporting and inhibiting factors. This research is a type of field research with a qualitative descriptive approach. The data analysis used is to select the data that has been obtained and then collected to be re-analyzed and ends at drawing conclusions. The results showed that the implementation of PAI learning in shaping the religious character of students at SMP Muhammadiyah 48 Medan through various school programs, including self-development, application in subjects, and integration in school culture through 5S activities and several other activities. Supporting factors in its implementation are adequate preparation, media support that can assist educators in providing directions to students to carry out routine religious activities, an attitude of caring and togetherness within each educator in shaping the character of students, and support from the surrounding environment. school. While the inhibiting factors are unsupportive association, family background/environment, the lack of role models regarding religion for students at home, and the lack of awareness in the religious aspects of students. Keywords: Character Education, Religious Character, Educational Implementation